SARS-CoV-2 Vaccination and Chilblain-like Lesions: What Do We Know So Far? - Shaikh, Taha Gul; Waseem, Summaiyya; Ahmed, Syed Hassan; Abdul Qadir, Nashwa; Piccolo, Vincenzo (Dermatology Practical & Conceptual, 2022)
The coronavirus pandemic has caused massive damage to global health care and the economy. COVID-19 vaccination and following the government protocols is the only way to tackle this situation. The vaccination program has been paced around the globe to return as soon as possible to pre-COVID time. Although all the vaccines have been approved after the rigorous clinical and safety trials, some adverse effects have surfaced and are being reported from different parts of the world. One such side effect is chilblain-like lesions following the COVID vaccination. Chilblain lesions, also known as pernio, are an inflammatory condition usually affecting the acral regions of the body. It is mostly reported from cold and damp areas and has multiple causes associated with it. Reporting of such similar lesions has raised concern amongst the scientific community and has led to vaccine hesitancy amongst the general population. The exact mechanism behind these lesions is still unknown. Although the incidence of this condition is low, it still requires attention from the authorities. This study aims to review the publicly available data and to provide concise and comprehensive information on chilblain-like lesions post-COVID-vaccination.